Biomasa, carbono y CO2 equivalente acumulado en una cronosecuencia de bosque seco tropical en el Parque Nacional Santa Rosa, Costa Rica y el Parque Estadual de Mata Seca, Brasil. - Calvo-Obando, Ana Julieta (Instituto Tecnológico de Costa Rica, 2017)
Abstract. The tropical dry forest (TDF) is one of the most threatened and least studied forest ecosystems in the world, so the estimation of its ecological value for its management and conservation represents a challenge with respect to other ecosystems. Research on carbon stocks in TDF is no exception as research has focused mainly on wet forests. This study aimed determine the accumulated biomass, carbon and CO2 equivalent, stored in a chronosequence of secondary TDF in the Neotropics, specifically at Santa Rosa National Park in Costa Rica and Mata Seca State Park in Brazil. This study was possible thanks to information provided from the Tecnológico de Costa Rica and Tropi Dry project trial of permanent sampling plots, which was established and monitored following a single protocol of research between countries. In both countries, it was possible to study: (a) three successional stages (early, intermediate and late), (b) two years 2006 and 2014, in which were sampled in Costa Rica 1067 and 1054 trees respectively, and in Brazil 1824 and 2173, (c) a total sampling of 29 plots of 1000 m2 each for a total area of 29 000 m2 over a period of eight years (9000 m2 in Costa Rica and 20000 m2 in Brazil). Moreover, this study characterizes the climate behavior in the two sites under analysis in order to understand more comprehensively the dynamics in both locations. Broadly, it was possible to determine that the aboveground and roots biomass, carbon and CO2 equivalent tend to increase from early stages to late stages of TDFs, in addition to doing so from year 2006 with respect to 2014. Furthermore, Santa Rosa National Park showed higher magnitudes at the three successional stages in regard to the Mata Seca State Park during the year 2006, as well as for the early and intermediate stages during the year 2014. Specifically, this study was able to estimate the following values of aboveground and root biomass, carbon and CO2 equivalent, all in Mg ha-1. At Costa Rica during the year 2006 the aboveground biomass was 41.3-181.0, the carbon 19.8-88.3 and the CO2 equivalent 72.7-324.1. While the root biomass was 9.2-34.3, the carbon 4.8-18.2 and the CO2 equivalent 17.5-66.7. In Brazil during the same year the aboveground biomass was 7.4-173.7, the carbon 3.4-84.7 and the CO2 equivalent 12.4-310.8. Meanwhile the root biomass was 2.0-32.9, the carbon 1.0-17.5 and the CO2 equivalent 3.7- 64.1. During year 2014, in Costa Rica the aboveground biomass was 60.9-205.4, the carbon 29.3-100.2 and the CO2 equivalent of 107.7-367.8. While the root biomass was 12.9-38.3, the carbon 6,7-20,3 and the CO2 equivalent 24.8-74.6. In Brazil during the same year the aboveground biomass was 59.5-208.0, the carbon 28.4-101.5 and the CO2 equivalent 104.3- 372.6. Meanwhile the root biomass was 12.7-38.7, the carbon 6.6-20.5 and the CO2 equivalent 24.2-75.4. While in terms of average annual productivity in Mg ha-1 year-1 of the aboveground CO2 equivalent, in Costa Rica it was 4.5, 7.1 and 5.6 in early, intermediate and late stage; Meanwhile in Brazil it was 12.0, 2.1 and 7.9 respectively. Regarding root CO2 equivalent values, in Costa Rica it was 0.9, 1.2 and 0.9 respectively at each stage of succession and in Brazil of 2.4, 0.4 and 1.3 respectively.

Resumen. El bosque seco tropical (BST) es uno de los ecosistemas forestales más amenazados y menos estudiados del mundo, por lo que la estimación de su valor ecológico para su manejo y conservación representa un reto con respecto a otros ecosistemas. La investigación sobre reservas de carbono en BST no son la excepción ya que la investigación se ha concentrado principalmente en los bosques húmedos. Por tanto, el objetivo de este estudio fue determinar la biomasa aérea (Ba) y de raíces (Br), el carbono (C) y el CO2 equivalente (CO2.eq) que se encuentra almacenado en una cronosecuencia de sucesión secundaria de BST en el Neotrópico, específicamente en el Parque Nacional Santa Rosa (PNSR) en Costa Rica y en el Parque Estadual Mata Seca (PEMS) en Brasil. Esto fue posible gracias a la información de campo de una red de parcelas permanentes de muestreo (PPM) que siguió el protocolo de investigación del grupo Tropi Dry y que fue establecida y monitoreada por el Tecnológico de Costa Rica y la Universidad Estadual de Montes Claros. Gracias a este protocolo único de investigación fue posible muestrear en los dos países: (a) tres estadios sucesionales (temprano, intermedio y tardío), (b) dos años 2006 y 2014, (c) un total de 1067 y 1054 árboles para cada año en Costa Rica; así como 1824 y 2173 árboles en Brasil, (d) 29 parcelas de 1000 m2 para un total de 29 000 m2 (9000 m2 en el PNSR y 20000 m2 en el PEMS). Además, este estudio caracterizó el comportamiento climático en los dos sitios bajo análisis con el objetivo de comprender de forma más integral su dinámica. Se logró determinar que Ba, Br, C y CO2.eq incrementan de bosques tempranos hacia bosques tardíos, además de hacerlo del año 2006 con respecto al año 2014. El PNSR presentó magnitudes superiores para los tres estadios de sucesión con respecto al PEMS durante el año 2006; así como para los estadios temprano e intermedio durante el año 2014. Específicamente este estudio fue capaz de determinar en función del estadio sucesional los siguientes valores, todos en Mg ha-1: (a) En Costa Rica durante el año 2006 la Ba fue de 41,3–181,0, el C de 19,8-88,3, el CO2.eq de 72,7- 324,1; mientras que la Br fue de 9,2–34,3, el C 4,8-18,2, el CO2.eq de 17,5-66,7. En Brasil durante el mismo año la Ba fue de 7,4-173,7, el C de 3,4-84,7 y el CO2.eq de 12,4-310,8; y la Br fue de 2,0-32,9, el C de 1,0-17,5 y el CO2.eq de 3,7-64,1. Por otro lado, para el año 2014, en Costa Rica la Ba fue de 60,9-205,4, el C de 29,3-100,2, el CO2.eq de 107,7-367,8. Mientras que la Br fue de 12,9-38,3, el C de 6,7-20,3, el CO2.eq de 24,8-74,6. En Brasil durante el mismo año la Ba fue de 59,5-208,0, el C de 28,4-101,5 y el CO2.eq de 104,3-372,6; y la Br fue de 12,7-38,7, el C de 6,6-20,5y el CO2.eq de 24,2-75,4. En términos de productividad promedio anual en Mg ha−1 año−1 del CO2.eq aéreo en Costa Rica fue de 4.5 en estadio temprano, 7.1 estadio intermedio y 5.6 en estadio tardío; mientras que en Brasil fue de 12.0, 2.1 y 7.9 para cada estadio respectivamente. A nivel de CO2.eq subterráneo de raíces, en Costa Rica fue de 0.9, 1.2 y 0.9 respectivamente en cada estadio de sucesión y en Brasil de 2.4, 0.4 y 1.3. Adicionalmente, este estudio da a conocer cuales familias y especies son las que actúan como los principales almacenes de CO2.eq aéreo en estos bosques. Con este trabajo se espera contribuir al estado del conocimiento que se tiene sobre este ecosistema específico y que la información generada contribuya en la toma de decisiones para asegurar su conservación y manejo.
Proyecto de Graduación (Maestría en Gestión de Recursos Naturales y Tecnologías de Producción) Instituto Tecnológico de Costa Rica. Área Académica Agroforestal, 2017.
Keywords: Restauración ecológica; Conservación; Bosques tropicales; Bosques secundarios; Servicios ambientales; Fijación del carbono